Food Security and Economic Growth: An Income Level Comparison - Máté, Domicián; Novotny, Ádám (International Journal of Engineering and Management Sciences, 2021)
Food security is a fundamental but often neglected aspect of economic growth and sustainable development. This paper examines the effect of food security on productivity (GDP/capita) over time, while taking the income level of various countries into account. Dynamic panel regression analyses suggest that food security is positively related to productivity, but this effect is stronger in more developed countries. The study highlights the complexity of the economic problems faced by the least developed countries, where increasing the consumption and supply of food is insufficient for significantly increasing economic performance.